Effects of noise exposure on young adults with normal audiograms I: electrophysiology - Prendergast, Garreth; Guest, Hannah; Munro, Kevin J.; Kluk, Karolina; Léger, Agnes; Hall, Deborah A.; Heinz, Michael G.; Plack, Christopher J. (Elsevier, 2017)
Noise-induced cochlear synaptopathy has been demonstrated in numerous rodent studies. In these animal models, the disorder is characterized by a reduction in amplitude of wave I of the auditory brainstem response (ABR) to high-level stimuli, whereas the response at threshold is unaffected. The aim of the present study was to determine if this disorder is prevalent in young adult humans with normal audiometric hearing. One hundred and twenty six participants (75 females) aged 18-36 were tested. Participants had a wide range of lifetime noise exposures as estimated by a structured interview. Audiometric thresholds did not differ across noise exposures up to 8 kHz, although 16- kHz audiometric thresholds were elevated with increasing noise exposure for females but not for males. ABRs were measured in response to high-pass (1.5 kHz) filtered clicks of 80 and 100 dB peSPL. Frequency-following responses (FFRs) were measured to 80 dB SPL pure tones from 240- 285 Hz, and to 80 dB SPL 4 kHz pure tones amplitude modulated at frequencies from 240-285 Hz (transposed tones). The bandwidth of the ABR stimuli and the carrier frequency of the transposed tones were chosen to target the 3-6 kHz characteristic frequency region which is usually associated with noise damage in humans. The results indicate no relation between noise exposure and the amplitude of the ABR. In particular, wave I of the ABR did not decrease with increasing noise exposure as predicted. ABR wave V latency increased with increasing noise exposure for the 80 dB peSPL click. High carrier-frequency (envelope) FFR amplitudes decreased as a function of noise exposure in males but not females. However, these correlations were not significant after the effects of age were controlled. The results suggest either that noise-induced cochlear synaptopathy is not a significant problem in young, audiometrically normal adults, or that the ABR and FFR are relatively insensitive to this disorder in young humans, although it is possible that the effects become more pronounced with age.